Mix Design Optimisation and Durability Study of High Performance Concrete Containing Micro and Nano Palm Oil Fuel Ash - Wan Hassan, Wan Nur Firdaus (Curtin University, 2019)
This study investigated the effect of micro and nano POFA as supplementary cementitious materials on the strength and durability properties of high-performance concrete. The study herein developed mathematical models to predict the workability and strengths properties of concrete containing micro and nano POFA. A numerical optimization was performed to obtain the optimal range of micro and nano POFA in the concrete mix design. Durability properties tests verified the significant effects of the optimum proposed binders in the design mix.